Penguatan Nilai Pendidikan Agama Hindu Pada Upacara Mekandang Dalam Rangkaian Manusa Yadnya Di Desa Barambai Kolam Kanan Kecamatan Barambai Kabupaten Barito Kuala - Rubi, Made; Supandi, I Nyoman Alit; Suryawan, I Gde (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
The Mekandang ceremony, which has been part of the ancestral heritage since ancient times, is carried out by every couple of lovers after having a child. The Mekandang Ceremony is held when the baby is 105 days old, or around three months old. Unique implementation At the Mekandang Ceremony, there are several processions performed at home. Execution The Mekandang Ceremony is carried out as a form of cleansing the body and soul of the baby, none other than as an expression of gratitude as well as asking for safety for the baby. Three issues are raised in this study: 1) How is the form of strengthening Hindu religious education in the Mekandang Ceremony In the network Manusa Yadnya? 2) What is the value of Hindu education found in the Mekandang Ceremony in the Manusa Yadnya network? 3) What are the implications of strengthening Hindu religious education through the Makandang Ceremony in the network Manusa Yadnya? Theories used to analyze the problem are: 1) Religion theory; 2) Value theory; and 3) Reciprocal Stimulus Theory. Methods of collecting data in this research are observation, interviews, literature study, and documentation. The data that has been collected was analyzed using a qualitative descriptive analysis method with data reduction, data presentation, and verification or conclusion steps. The results of the study show that: 1) Forms of strengthening Hindu religious education in Mekandang Ceremony are divided into several stages, namely: reinforcement sraddha bhakti,principle strengthening menyame braya, strengthening the principle of environmental awareness, and strengthening the universal value of religion in Mekandang Ceremony in the village of Barambai Kolam Kanan, 2) The value of Hindu religious education found in Mekandang Ceremony, namely: Tattwa Values, Moral/Ethical Values, Ceremonial Values, and Aesthetic Values, 3) Implications in Strengthening Hindu Religious Education at the Mekandang Ceremony, namely: Theological Implications, Social Implications, and educational Implications for the Mekandang Ceremony